The mechanics of diurnal thermal stratification in river pools: Implications for water management and species conservation - Buxton, Todd H.; Lai, Yong G.; Som, Nicholas A.; Peterson, Eric; Abban, Ben (Hydrological processes, 2022)
We examined conditions that form or prevent thermal stratification in river pools using field measurements, statistical modelling, and three‐dimensional (3D) computational fluid dynamics (CFD) modelling. Our motivation is to identify variables that control stratification for exploitation to enhance or prevent thermal gradients as needed to benefit species in rivers. One study pool (UT) is located above water storage reservoirs and receives natural flows, and the other pool (PT) is regulated and receives unnaturally high, cold water in summer; both pools are on the Trinity River, California. Thermal stratification formed in UT pool in spring at a critical flow of 1.01 m3/s, peaked at 8.1°C in summer, and exhibited diurnal formation and destruction under sub‐critical flows until fall. At PT pool, the 14.2 m3/s baseflow caused mixing that prevented stratification and formed a spatially homogenous thermal environment. Statistical analyses indicated the daily range in air and inlet water temperature at UT pool best correlated with the occurrence and strength of stratification but were progressively irrelevant as flows increased above the critical value. The validated CFD model was used to reproduce the diurnal stratification and explain the processes involved. The CFD model correctly predicted the observed critical flow and replicated the dynamics of stratification at UT pool and isohyets observed at PT pool. The CFD results also confirmed that low flows are the main variable for stratification to form, and the daily range in inlet water temperature drives the strength of the thermal gradient. The model estimated a critical discharge at PT pool of 2.0 m3/s, twice that for UT pool owing to its 2.6‐times larger area, suggesting critical flows scale with pool size. Results showed that releasing critical and lower flows in summer on regulated streams may conserve water and provide thermal gradients that benefit poikilothermic species; alternately, higher than critical flows can prevent stratification where needed to improve water quality. Diurnal thermal stratification in river pools results from diurnal variations in inlet water temperatures and low discharges; it may be utilised to benefit the ecology of the river system. Combined field study, statistical modelling and computational fluid dynamics modelling are used to show the existence of a critical flow at each pool below which thermal stratification forms. Results show summer flows may be lowered on regulated streams to conserve water and provide thermal gradients that benefit poikilothermic species; alternately, higher than critical flows may be released to prevent stratification where needed to improve water quality.